Hubungan Karakteristik Sosio-Demografi dengan Penggunaan Tubektomi pada Peserta KB Wanita di Indonesia - Yessi Febriana; Adik Wibowo (Jurnal Kesehatan Komunitas, 2022)
The proportion of long-term and permanent contraceptive methods used among women in Indonesia, namely tubectomy, is still very low at 2,4 percent. Various research studies show that socio-demographic factors have influenced the choice of tubectomy as a contraceptive method for women. This study aims to determine the relationship between socio-demographic characteristics and tubectomy used on women as family planning participants in Indonesia by utilizing the 2017 Indonesia Demographic Health Survey (IDHS). Cross-sectional was implemented for the research, from 49.627 women of childbearing age, the sample of 19,964 respondents was taken. Bivariate analysis and logistic regression were conducted to analyze the relationship between selected socio-demographic factors and the dependent variable. The study shows that the number of living children is the most significant association with the use of tubectomy (p-value = 0.005; OR = 6.07). Other factors that also related are the age group of 25-34 years (p-value = 0.005; OR = 0.034), rural area (p-value = 0.005; OR = 0.525), lower-middle economic status (p-value = 0.005; OR = 0.906), status of working women (p-value = 0.005; OR = 1.288), ideal number of children is 3 or more (p-value = 0.005; OR = 1.547), family planning decisions are made together between husband and respondents (p-value = 0.005; OR = 0.327), and women's knowledge around 8 types of contraception or more (p-value = 0.005; OR = 2.017). The choice of tubectomy by female family planning participants is related to socio-demographic factors (number of living children, age, residence, employment status, the ideal number of children, family planning decision, and women’s knowledge). It is recommended that the family planning fieldworker/cader use influential socio-demographic characteristics for identifying, mapping, and targeting prospective tubectomy participants so that information on tubectomy contraceptive methods is carried out on target.